Revision of the genera Eutrecha and Xenotrecha (Solifugae: Ammotrechidae), taxonomic notes on Ammotrechinae, and description of a remarkable new Eutrecha from Colombia - Botero Trujillo, Ricardo (2023)
The solifuge genera Eutrecha Maury, 1982 and Xenotrecha Maury, 1982 are among the rarest and most elusive groups of camel spiders in the New World. Since their inception, both genera have remained unclassified within the subfamilial scheme of Ammotrechidae, where they belong, and their systematic position and affinities to other genera continue to be unexplored. This contribution addresses the affinities that Eutrecha and Xenotrecha have to the type genus of Ammotrechinae, Ammotrecha Banks, 1900. Based on the taxonomic distribution of characters shared by these genera, it is proposed that the three are closely related and classified into Ammotrechinae. Revised diagnoses are presented for Ammotrechinae sensu stricto, Eutrecha, and Xenotrecha, and redescriptions are presented for species of these genera, when possible. A new species, Eutrecha belenensis, sp. nov., is described from Colombia, raising to three the number of species in the genus. New material of Eutrecha florezi Villareal-Blanco, Armas and Martínez, 2017 and Xenotrecha huebneri (Kraepelin, 1899) is referenced, thus extending the distribution range of these species in Colombia and Brazil, respectively. Ammotrechinae sensu stricto is here defined by the presence of a retroventral longitudinal carina on the movable finger of the chelicerae and a cleavage plane basally on the femur of pedipalps, among other characters. The cleavage plane allows the pedipalp to be autotomized, representing the first report of pedipalp autotomy in Solifugae. This work also presents a discussion on the taxonomy of Ammotrechidae and delves into some aspects that affect the current delimitation of some of its subfamilies.